2017
DOI: 10.1038/ncomms15410
|View full text |Cite
|
Sign up to set email alerts
|

Mistranslation can enhance fitness through purging of deleterious mutations

Abstract: Phenotypic mutations are amino acid changes caused by mistranslation. How phenotypic mutations affect the adaptive evolution of new protein functions is unknown. Here we evolve the antibiotic resistance protein TEM-1 towards resistance on the antibiotic cefotaxime in an Escherichia coli strain with a high mistranslation rate. TEM-1 populations evolved in such strains endow host cells with a general growth advantage, not only on cefotaxime but also on several other antibiotics that ancestral TEM-1 had been unab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…To understand how the additional mutations in the LL lines constrain adaptation, we performed a few further analyses. Because mutations G238S, E104K, and M182T were selected in the LL lines, as well as in previous studies (16,24,27,30,31), we first asked whether allele SL2 is selectively accessible from the genotype containing these three mutations, using two independent analyses. We first constructed and analyzed the resistance landscape connecting threefold mutant E104K/M182T/G238S and the genotype containing the six nonsynonymous mutations of final allele SL2 (neglecting synonymous mutation G143* obtained in round 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how the additional mutations in the LL lines constrain adaptation, we performed a few further analyses. Because mutations G238S, E104K, and M182T were selected in the LL lines, as well as in previous studies (16,24,27,30,31), we first asked whether allele SL2 is selectively accessible from the genotype containing these three mutations, using two independent analyses. We first constructed and analyzed the resistance landscape connecting threefold mutant E104K/M182T/G238S and the genotype containing the six nonsynonymous mutations of final allele SL2 (neglecting synonymous mutation G143* obtained in round 5).…”
Section: Resultsmentioning
confidence: 99%
“…Not only could clinical patterns of molecular evolution be recapitulated in the laboratory (22,23), TEM-1 has also been used to address basic evolutionary questions. For example, recent work with TEM-1 revealed molecular details that determine its evolvability (14,(24)(25)(26)(27)(28), and showed that its fitness landscape is rugged (16,27,29,30). This causes TEM alleles selected from large mutation supplies to often follow the same trajectory involving three common mutations (16).…”
Section: Significancementioning
confidence: 99%
“…In addition, compared to prior work our results are somewhat more applicable to E. coli function and evolution in natural ecosystems. For instance, the ecological relevance of genetic manipulations used in prior work (such as mutations in the ribosomal protein S4 (Fan et al 2015;Bratulic et al 2017)) is unclear. In contrast, translation -and specifically translation initiation -is reduced in response to several environmental stresses (Nagase et al 1988;Winther and Gerdes 2011;Watanabe et al 2013), creating a cellular environment analogous to that of our mistranslating mutant with reduced initiator tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while our experiments inform about the short-term impact of altering mistranslation, the longer-term impacts of mistranslation need to be investigated further. For instance, recent work showed that a mistranslating strain fixes distinct sets of beneficial mutations during laboratory adaptation to antibiotic stress (Bratulic et al 2017). It would be exciting if these results could be generalized across various stresses and forms of mistranslation.…”
Section: Discussionmentioning
confidence: 99%
“…It this case, mistranslation is beneficial in response to environmental stresses as it can help sustain and disseminate cellular phenotypic viability, e.g. as it may enhance pathogens survival by creating antigenic diversity in surface proteins 15 On an evolutionary time scales too, phenotypic errors might open evolutionary paths otherwise precluded by epistatic interactions 16 , and facilitate the purging of deleterious mutations 17 . A computational analysis of codon usage patterns across genomes revealed that natural selection constrains the identity of codons at evolutionarily conserved positions, suggesting that evolution favors more accurate codons at these sites 18 .…”
Section: Introductionmentioning
confidence: 99%